Model pendampingan manajemen masjid ramah anak dan aman Covid-19 di Masjid Al-Musthofa Dusun Jaten, Sendangadi, Mlati, Sleman - Fajar Fandi Atmaja; Syaifulloh Yusuf (Penerbit Goodwood, 2021)
Purpose: This community service aimed to strengthen human resources for takmir (mosque manager), mosque youth, parents, and the community in implementing a child-friendly and Covid-19 safe mosque management system. Method: The method used in this community event was Focus Group Discussion, training, and practice. These three methods were used to accommodate the community services. Results: The results of this community service show that the participants understand, know, and use the facilities wisely which established the child-friendly and Covid-19 safe mosque management system. Conclusions: This service is strengthening the human resources of takmirs, mosque youth, parents and the community. The activities carried out are training for mosque management, training for TPA teachers, establishing a children's reading corner, installing Wifi, and establishing a child-friendly and safe Covid-19 mosque organization board. Keywords: Mosque management, Child-friendly, Covid-19 safe, Educational character